Positional cloning and characterization reveal the role of a miRNA precursor gene ZmLRT in the regulation of lateral root number and drought tolerance in maize. Issue 3 (31st December 2022) - Zhang, Ming; Chen, Yanhong; Xing, Hongyan; Ke, Wensheng; Shi, Yunlu; Sui, Zhipeng; Xu, Ruibin; Gao, Lulu; Guo, Ganggang; Li, Jiansheng; Xing, Jiewen; Zhang, Yirong
Abstract: Lateral roots play essential roles in drought tolerance in maize ( Zea mays L.). However, the genetic basis for the variation in the number of lateral roots in maize remains elusive. Here, we identified a major quantitative trait locus (QTL), qLRT5‐1, controlling lateral root number using a recombinant inbred population from a cross between the maize lines Zong3 (with many lateral roots) and 87‐1 (with few lateral roots). Fine‐mapping and functional analysis determined that the candidate gene for qLRT5‐1, ZmLRT, expresses the primary transcript for the microRNA miR166a. ZmLRT was highly expressed in root tips and lateral root primordia, and knockout and overexpression of ZmLRT increased and decreased lateral root number, respectively. Compared with 87‐1, the ZmLRT gene model of Zong3 lacked the second and third exons and contained a 14 bp deletion at the junction between the first exon and intron, which altered the splicing site. In addition, ZmLRT expression was significantly lower in Zong3 than in 87‐1, which might be attributed to the insertions of a transposon and over large DNA fragments in the Zong3 ZmLRT promoter region. These mutations decreased the abundance of mature miR166a in Zong3, resulting in increased lateral roots at the seedling stage. Furthermore, miR166a post‐transcriptionally repressed five development‐related class‐III homeodomain‐leucine zipper genes. Moreover, knockout of ZmLRT enhanced drought tolerance of maize seedlings. Our study furthers our understanding of the genetic basis of lateral root number variation in maize and highlights ZmLRT as a target for improving drought tolerance in maize. Abstract : Knockout of the miR166a precursor gene ZmLRT significantly enhanced drought tolerance of maize seedlings, suggesting that ZmLRT could be used as a target for engineering drought tolerance in maize.